Screening and diversity analysis of Dibutyl phthalate degrading bacteria in agricultural soil in Chengdu, China. - Yong Li; Sidan Gong; Huan Liu; Yajie Li (PLoS ONE)
Dibutyl phthalate (DBP) with teratogenicity, carcinogenesis, and mutagenesis, is a ubiquitous endocrine disruptor in the environment. The widespread usage of plastic mulch has resulted in a severe DBP pollution problem in agricultural soil. One of the most vital ways to mitigate the DBP pollution problem is to use DBP degrading bacteria to reduce the concentration of DBP in agricultural soil. DBP degrading bacteria studied in previous studies mainly come from sewage treatment plants, rivers, landfills, bioreactors, and other environmental media. At the same time, there was relatively little research on DBP degrading bacteria in agricultural soil. Therefore, using the pure culture approach, the candidate DBP degrading strains were isolated and screened from vegetable plots contaminated with plastic mulch in Dayi County, Chengdu City, Sichuan Province, China. The taxonomy of the strains was determined using the 16 sedimentation ribosomal deoxyribonucleic acid (16S rDNA) molecular technique. Furthermore, ultraviolet and visible spectrophotometry and high performance liquid chromatography (HPLC) were used to assess the degrading capability of strains. The findings showed that a total of twenty-six DBP degrading strains were screened from vegetable plots contaminated with plastic mulch in Dayi County, Chengdu City, Sichuan Province, China, and these strains belonged to two phyla: Proteobacteria and Bacillota, eight families, including Pseudomonas, Enterobacteriaceae, and Bacillaceae, as well as ten genera, such as Enterobacter, Pseudomonas, and Bacillus. One of them, the strain SWDB-7 was a potentially new species in the Enterobacter genus. The most prominent genus of the isolated strains was Enterobacter. There were significant variations in the degradation capability of different obtained DBP degrading strains. and their degradation efficiency was 14.12%-91.86%. With a total DBP removal rate of 91.86%, strain SWDB-15 had the most effective degrading capability among them. To sum up, the DBP degrading strains in vegetable plots contaminated with plastic mulch in Dayi County, Chengdu City, Sichuan Province, China are rich in diversity and capable of breaking down DBP.